2015
DOI: 10.1007/s11145-015-9593-9
|View full text |Cite
|
Sign up to set email alerts
|

Dialect variation, dialect-shifting, and reading comprehension in second grade

Abstract: The purpose of this study was to examine second graders’ (n=680) changing spoken nonmainstream American English (NMAE) use in relation to their oral language and reading comprehension achievement. Fall NMAE production was negatively associated with fall achievement scores. NMAE production generally decreased from fall to spring. Students who qualified for the US Free and Reduced Lunch program (FARL) and who had stronger language skills were more likely to decrease their NMAE use (i.e., dialect shifting) than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
(84 reference statements)
1
22
0
1
Order By: Relevance
“…For example, in large cross-sectional studies using spoken narratives and picture description tasks, Craig et al (2009) observed decreasing spoken production of AAE forms among children from first through fifth grades (ages 6-11 years), with the greatest decreases noted in first grade (Craig et al, 2009;. In separate longitudinal studies using the same measure of spoken dialect production at all time points, researchers observed significant decreases in spoken NMAE production rates between kindergarten and first grade (Ortiz et al, 2012;, during the first grade , between first grade and second grade (Terry et al, 2012), and during second grade (Terry et al, 2016). Importantly, in each of these studies, most children were observed to change their dialect use spontaneously and without explicit instruction.…”
Section: Young Children Dialect Shift Over Timementioning
confidence: 98%
See 4 more Smart Citations
“…For example, in large cross-sectional studies using spoken narratives and picture description tasks, Craig et al (2009) observed decreasing spoken production of AAE forms among children from first through fifth grades (ages 6-11 years), with the greatest decreases noted in first grade (Craig et al, 2009;. In separate longitudinal studies using the same measure of spoken dialect production at all time points, researchers observed significant decreases in spoken NMAE production rates between kindergarten and first grade (Ortiz et al, 2012;, during the first grade , between first grade and second grade (Terry et al, 2012), and during second grade (Terry et al, 2016). Importantly, in each of these studies, most children were observed to change their dialect use spontaneously and without explicit instruction.…”
Section: Young Children Dialect Shift Over Timementioning
confidence: 98%
“…Finally, there is evidence that children who demonstrate shifting from more to less NMAE use during early schooling may have stronger language, reading, and writing skills. For example, in three longitudinal studies with primary grade children, researchers found that dialect shifting was predicted by performance on oral language measures, such as vocabulary, morphosyntax, and phonological awareness (Terry et al, 2012(Terry et al, , 2016Craig et al, 2014). Terry and colleagues also found that children who shifted from more to less NMAE use during first and second grade demonstrated greater gains in word reading and reading comprehension at the end of the school year (Terry et al, 2012(Terry et al, , 2016.…”
Section: Young Children's Dialect Shifting Is Related To Language Andmentioning
confidence: 99%
See 3 more Smart Citations